ANALISIS PERILAKU.PETANI TERHADAP RISIKO USAHATANI LIDAH BUAYA DI PONTIANAK - Imelda Imelda; Jangkung Handoyo Mulyo; Dwidjono Hadi Darwanto (Agro Ekonomi, 2008)
The research aims to: (1) identify the income differences between Aloe vera farming system with monoculture and multicultural cropping pattern; (2) identify the risk of cost, production, and income of Aloe Vera farming of each cropping pattern, (3) identify farmer behavior to the risk of each Aloe Vera farming system, and (4) determine socio-economic factors influencing the farmer behavior to the risk of Aloe Vera farming .. Research area was chosen by purposive in North 'Pontianak sub-district, West Kalimantan. Analyses used were cost and income analysis, coefficient of variation analysis, quadratic utility function, and multiple linear regressions. The results show that the Aloe Vera farmer income with monoculture cropping pattern is lower than Aloe Vera farmer with multicultural. The risk of cost, ,production, and income of Aloe Vera farming with monoculture cropping pattern is higher than multicultural. 40.74% Aloe Vera farmers with monoculture cropping pattern and 7.89% Aloe Vera farmers with multicultural show behavioral risk lover. There are 14.82% Aloe Vera farmers with monoculture cropping pattern and 28.95% Aloe Vera farmers with multicultural show behavioral risk averse. The remaining were risk neutral farmers, i.e. 44, 44% Aloe Vera farmers with monoculture cropping pattern and 63,16% Aloe Verafarmers with multicultural. Farmer behavior to the risk influenced by farmer's age, family size, farmer's experience, and dummy of cropping pattern and farmer ethnical.